2022
DOI: 10.3389/fpsyg.2022.860603
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Foreign Language Classroom Anxiety, Enjoyment, and Expectancy-Value Motivation and Their Predictive Effects on Chinese High School Students’ Self-Rated Foreign Language Proficiency

Abstract: The present study explored the relations among foreign language (FL) classroom anxiety, enjoyment, expectancy-value motivation, and their predictive effects on Chinese high school students’ self-rated FL proficiency. Participants were 280 senior high school Chinese English as a foreign language learners who were surveyed on their foreign language classroom anxiety (FLCA), foreign language enjoyment (FLE), and expectancy-value motivation. Results showed that (1) the students generally experienced a medium to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 65 publications
(144 reference statements)
3
29
1
1
Order By: Relevance
“… Nagle (2021) found that students’ willingness to communicate in Spanish was predicted by their attainment value and intrinsic value, and that the course achievement was predicted by their expectancy beliefs. Dong et al’s (2022) study revealed a complex correlation between the students’ FL classroom anxiety and expectancy-value motivation: As the students’ FL classroom anxiety increased, their expectancy beliefs, intrinsic value, attainment value, and utility value decreased, but their cost value increased.…”
Section: Literature Reviewmentioning
confidence: 95%
See 4 more Smart Citations
“… Nagle (2021) found that students’ willingness to communicate in Spanish was predicted by their attainment value and intrinsic value, and that the course achievement was predicted by their expectancy beliefs. Dong et al’s (2022) study revealed a complex correlation between the students’ FL classroom anxiety and expectancy-value motivation: As the students’ FL classroom anxiety increased, their expectancy beliefs, intrinsic value, attainment value, and utility value decreased, but their cost value increased.…”
Section: Literature Reviewmentioning
confidence: 95%
“…For example, Gong et al (2020) and Liu and Zhang (2022) found that contact with native speakers increased participants’ interest in and motivation to learn the target language, which led to enhanced proficiency in the language. Dong et al (2022) found that learners with lower anxiety and greater motivation usually performed better in the target language than those with greater anxiety and lower motivation. This might be because motivation offers second language learners the stimulus to start learning and encourages them to keep learning without feeling reluctant, and eventually helps them to meet their goals ( Dörnyei, 2005 ).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations